Enhanced Healing and Antimicrobial Efficacy of Chitosan-g-Polyacrylamide in a Rat Model of Gingival Ulcers - Zheng, Yanfen; Ke, Lingjie; Lu, Yin; Zuo, Qiliang; Deng, Guanhong; Wang, Hairui; Zeng, Xiamei (Frontiers in Chemistry, 2020)
Patients in dental hospitals often experience oral ulcerative lesions, which lead to pain and affect the patient’s quality of life. At present, the goal of treating oral ulcerative lesions with drugs is to reduce inflammation and promote ulcer healing. However, very few antibacterial and hemostatic drugs are designed to be suitable for the microenvironment of gingival ulcers. Based on this, we have designed a natural therapeutic agent for oral ulcerative lesions that meets the various requirements of oral ulcerative lesion medication. The chitosan-g-polyacrylamide (CP) copolymer is composed of chitosan as the main chain and polyacrylamide polymers as the side chains. Antibacterial experiments show that this polymer can effectively inhibit the proliferation of Gram-negative (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus). In vitro cell experiments also show that the CP copolymer is non-toxic, which is conducive to ulcer wound healing. Coagulation experiments prove that the CP copolymer can accelerate blood coagulation to stop bleeding. In experiments using a Wistar rat gingival ulcer model, the CP copolymer significantly promoted ulcer healing and shorten the healing time. These results indicate that the CP copolymer may serve as a potential therapeutic agent for oral ulcerative lesions.